IMPLIKASI SERTIFIKAT HALAL PRODUK DALAM SAKRALISASI AGAMA DI INDONESIA - Cindy Fatimah; Surawan Surawan; Nurul Wahdah (UIN ANTASARI BANJARMASIN, 2022)
Abstract This paper aims to determine the implications of halal product certification in the sacralization of religion in Indonesia. Halal certification of the product itself is familiar to business people around the world, especially Indonesia. This paper uses a qualitative descriptive approach through a literature review of halal certification practices in Indonesia. The data were obtained from various articles, magazines, books and media about halal certification and related institutions, namely LPPOM MUI (Indonesian Food, Drug and Cosmetics Institute). The results of this study will describe the halal logo certification, its formation, certification stages, and products that must be halal certified. This article also shows that halal certification is related to the sacralization of Indonesian religion. The implications of product halal certification in the sanctity of Indonesian religion, halal certification does not only sanctify a religion, but also provides guarantees, protection, and provides information about the official halal of a product. Halal certification also affects consumer confidence in halal-certified products for consumption because they have the loyalty and legality of the products consumed and used.Keywords: Halal certification; Religion; Indonesia. Abstract Tulisan ini bertujuan untuk mengetahui implikasi sertifikasi produk halal dalam sakralisasi agama di Indonesia. Sertifikasi halal produk sendiri sudah tidak asing oleh para pebisnis di seluruh dunia, khususnya Indonesia. Tulisan ini menggunakan pendekatan deskriptif kualitatif melalui kajian literatur praktik sertifikasi halal di Indonesia. Adapun data diperoleh dari berbagai artikel, majalah, buku dan media tentang sertifikasi halal dan lembaga terkait, yaitu LPPOM MUI (Lembaga Pangan, Obat dan Kosmetika Indonesia). Hasil penelitian ini akan memaparkan sertifikasi logo halal, pembentukannya, tahap sertifikasi, dan produk yang harus bersertifikat halal. Artikel ini juga menunjukkan bahwa sertifikasi halal berkaitan dengan sakralisasi agama Indonesia. Implikasi sertifikasi halal produk dalam kesucian agama Indonesia, sertifikasi halal tidak hanya menyakralkan suatu agama, tetapi jugamemberikan jaminan, perlindungan, dan pemberian informasi mengenai halal resmi suatu produk. Sertifikasi halal juga mempengaruhi kepercayaan konsumen pada produk bersertifikat halal untuk dikonsumsi karena memiliki loyalitas dan legalitas produk yang dikonsumsi dan digunakan. Keywords: Sertifikasi halal; Agama; Indonesia.